Harnessing the integrated stress response for the treatment of multiple sclerosis. Issue 4 (April 2016) - Way, Sharon W; Popko, Brian
Summary: Multiple sclerosis is a chronic demyelinating autoimmune disease of the CNS with no known cure. Although 12 immunomodulatory therapies exist, they have only modest effects on disease progression. The field has therefore focused on the development of alternative treatment strategies, such as enhancement of remyelination and CNS repair. Progress has been made on a third, complementary treatment approach that aims to protect oligodendrocytes—and the myelin they generate and maintain—from inflammation-mediated death by enhancing the integrated stress response. Studies in cells and in mouse models of multiple sclerosis have shown that this innate protective pathway, which maintains proteostasis, can be harnessed effectively to protect oligodendrocytes and myelin during inflammation. With one drug already in clinical development for patients with multiple sclerosis, and several potential therapies under investigation, modulation of the integrated stress response might become an important component of strategies to halt the progression of the disease.